The Efficacy and Safety of Esmolol for Septic Shock: A Systematic Review and Meta-analysis of Randomized Controlled Trials - Po Huang; Xiangchun Zheng; Zhi Liu; Xiaolei Fang (Frontiers Media S.A., 2021)
Purpose: The meta-analysis aims to identify whether septic shock patients can benefit from esmolol.Materials and Methods: The relevant studies from MEDLINE, Cochrane Library, Embase were searched by two independent investigators using a variety of keywords. Stata software (version 12.0, Stata Corp LP, College Station, TX, United States)was used for statistical analysis.Results: A total of 14 studies were identified and incorporated into the meta-analysis. For overall analysis, the treatment of esmolol was associated with decreased 28-day mortality (RR = 0.66, 95% CI = 0.56-0.77, p < 0.001). Meanwhile, our analysis found that, esmolol could decrease HR (SMD: −1.70; 95% CI: [−2.24−(−1.17)], cTnI (SMD: −1.61; 95% CI: [−2.06−(−1.16)] compared with standard treatment. No significant differences between the two groups were found in MAP, Lac, CI, and SVI.Conclusion: The findings of this meta-analysis intend to demonstrate that septic shock patients with high heart beats rate might be benefit from esmolol treatment despite enough fluid resuscitation. While, dependent on the study published, with the further development of septic shock, the positive impact of esmolol varies. The appropriate heart rate change interval cannot be confirmed, further high-quality and large-scale RCTs should be performed to verify it and screening more suitable heart rate levels.Systematic Review Registration: CRD42021239513